The GTPase Rho has a critical regulatory role in thymus development. - Henning, S W (1997)
The present study employs a genetic approach to explore the role of Rho GTPases in murine thymic development. Inactivation of Rho function in the thymus was achieved by thymic targeting of a transgene encoding C3 transferase from Clostridium botulinum which selectively ADP-ribosylates Rho within its effector domain and thereby abolishes its biological function. Thymi lacking functional Rho isolated from C3 transgenic mice were strikingly smaller and showed a marked (90%) decrease in cellularity compared with their normal litter mates. We also observed a similar decrease in levels of peripheral T cells in C3 transgenic mice. Analysis of the maturation status of thymocytes indicated that differentiation of progenitor cells to mature T cells can occur in the absence of Rho function, and both positive and negative selection of T cells appear to be intact. However, transgenic mice that lack Rho function in the thymus show maturational, proliferative and cell survival defects during T-cell development that severely impair the generation of normal numbers of thymocytes and mature peripheral T cells. The present study thus identifies a role for Rho-dependent signalling pathways in thymocyte development. The data show that the function of Rho GTPases is critical for the proliferative expansion of thymocytes. This defines a selective role for the GTPase Rho in early thymic development as a critical integrator of proliferation and cell survival signals.